Walking side‐by‐side: Supporting Aboriginal and Torres Strait Islander Australians to lead the way in alcohol research. (4th August 2022) - Lee, K. S. Kylie; Wilson, Scott; Stearne, Annalee E.; Hayman, Noel; Conigrave, James H.; Doyle, Michael; Bullen, Lynette; Weatherall, Teagan J.; James, Doug; Reynolds, Taleah; Perry, Jimmy; Conigrave, Katherine M.; et al.
Abstract: Several initiatives have sought to increase the number of First Nations individuals with a higher degree in research (i.e., PhD or research masters)—in Australia and in similarly colonised countries. However, little has been written on day‐to‐day support structures and mechanisms that might help First Nations Australian candidates thrive in postgraduate research degrees and beyond. For sensitive research fields such as alcohol, emerging Aboriginal and Torres Strait Islander researchers must grapple with topics which are stigmatising and in some instances associated with traumatic associations. There is also a lack of studies internationally that describe optimal support for First Nations students undertaking a higher degree by research with a primary focus on alcohol. Here we discuss what we have learned from the support offered through the Centre of Research Excellence in Indigenous Health and Alcohol—from the perspective of academic staff, students, trainees and early career researchers. We consider what may be generalisable lessons from this experience.